High Power Sodium-Ion Batteries and Hybrid Electrochemical Capacitors Using Mo or Nb-Doped Nano-Titania Anodes. Issue 9 (6th June 2018) - Bauer, Dustin; Roberts, Alexander J.; Patnaik, Sai Gourang; Brett, Dan J. L.; Shearing, Paul R.; Kendrick, Emma; Matsumi, Noriyoshi; Darr, Jawwad A.
Abstract : Nano-sized anatase (TiO2 ) and doped anatase (Mo0.1 Ti0.9 O2 and Nb0.25 Ti0.75 O2 ) materials (ca. 5 nm) were synthesized using continuous hydrothermal flow synthesis and evaluated as negative electrodes in Na-ion batteries and hybrid capacitors. Na-ion half-cells (vs. Na metal counter electrodes) for the Mo-doped titania (Mo0.1 Ti0.9 O2 ) and Nb-doped titania (Nb0.25 Ti0.75 O2 ) electrodes both showed significantly higher specific discharge capacities than undoped anatase (ca. 75 mAh g −1 compared to only 30 mAh g −1 for undoped TiO2 at 1 A g −1 ). This improved performance was attributed to higher pseudocapacitive contributions to charge storage, as well as improved sodium ion diffusion and lower charge transfer resistance. Na-ion hybrid electrochemical capacitors (Na-HECs) were made from the electrodes with activated carbon positive electrodes. As expected, Na-HECs using doped titania showed superior performance to the undoped anatase, with power densities up to 10.5 kW kg −1 or energy densities of over 60 Wh kg −1 (based on the weight of active material in both anode and cathode). The Mo0.1 Ti0.9 O2 /AC Na-ion hybrid capacitor also showed excellent specific capacitance retention of ca. 75% over 3000 cycles at 5 mA cm −2 (1 A g −1 ).